ISO 9001 & 14001: A Relationship with GDP? - Mills, T (2011)
This research was carried out to build on previous work regarding the drivers and diffusion patterns of ISO 9001/14001 global standards, designed by the International Organisation for Standardisation to set a benchmark for quality and environmental management systems respectively. The research looks to identify a link between total GDP growth in chosen economies and what affect this has on the uptake of the ISO 9001/14001 certifications and if successful will aid in the prediction of future ISO standards’ growth or decline. The economies focused on are those that are listed by ISO as the countries with the top ten highest numbers of ISO 9001 and ISO 14001 certifications, with China, Italy, Japan, Spain, Germany, UK, USA and South Korea appearing in both lists, Russia and India in the ISO 9001 top ten only, and Romania and the Czech Republic in the ISO 14001 top ten only. The countries were analysed using a combination of visual graphical evidence and Pearson’s correlation coefficients estimates and it was found that those countries with developing economies showed a trend towards a relationship between increased total GDP growth and increased certifications, whereas developed economies with slower total GDP growth showed a propensity for saturating or falling levels of certifications. The results of this study aid as an introduction to a new area of research and can be used as the basis for research of greater scope in terms of time-frame and economies analysed.